PENINGKATAN PRODUKTIVITAS KAMBING MELALUI TEKNOLOGI PAKAN DI KELOMPOK PKH DESA TEMPAK, CANDIMULYO, MAGELANG - Nur Rasminati; Setyo Utomo (DHARMA BAKTI, 2020)
This activities was aimed to improving the productivity of local goat throughimprovements of feed technologies. Location devotion in Tempak village, Candimulyo.Stages of activities were started from counseling, training, demonstration plots andmentoring. The number of participants were 20 farmers. The feed improvement was madethrough feed processing technology using local raw materials. Microbial starter isderived from rice fermented. As a nutritional supplement, local ingredients such as garlic,ginger, turmeric, bamboo shoots and banana are also fermented. Making silage using ricemicrobial and nutritional supplement produces good silage, with a fresh green color andfragrance. 100% farmer has made a rice microbial starter and nutritional supplement, butthat has been consciously practicing regularly and applying is 85%.